The Nordic maintenance care program: maintenance care reduces the number of days with pain in acute episodes and increases the length of pain free periods for dysfunctional patients with recurrent and persistent low back pain - a secondary analysis of a pragmatic randomized controlled trial - Andreas Eklund; Jan Hagberg; Irene Jensen; Charlotte Leboeuf-Yde; Alice Kongsted; Peter Lövgren; Mattias Jonsson; Jakob Petersen-Klingberg; Christian Calvert; Iben Axén (Chiropractic & Manual Therapies, 2020)
Abstract Background A recent study showed that chiropractic patients had fewer days with bothersome (activity-limiting) low back pain (LBP) when receiving care at regular pre-planned intervals regardless of symptoms (‘maintenance care’, MC) compared to receiving treatment only with a new episode of LBP. Benefit varied across psychological subgroups. The aims of this study were to investigate 1) pain trajectories around treatments, 2) recurrence of new episodes of LBP, and 3) length of consecutive pain-free periods and total number of pain-free weeks, for all study participants as well as for each psychological subgroup. Methods A secondary analysis of data from a randomized controlled trial of patients (n = 319) seeking chiropractic care for recurrent or persistent LBP used 52 weekly estimates of days with bothersome (activity-limiting) LBP. First, a generalized estimating equations analysis was used to compare the pain trajectory before and after the initial treatment in every new treatment period. Thereafter, a time-to-event analysis (using Cox regression) estimated time to/risk of a new LBP episode. The analyses were performed on i) all study participants and ii) separately for each psychological sub-group (named adaptive copers, interpersonally distressed and dysfunctional) classified by the West Haven-Yale Multidimensional Pain Inventory. Results Patients receiving MC had flat pain trajectories around each new treatment period and reported fewer days with pain compared to patients receiving the control intervention. The entire effect was attributed to the dysfunctional subgroup who reported fewer days with activity limiting pain within each new LBP episode as well as longer total pain-free periods between episodes with a difference of 9.8 weeks (CI 95% 3.3, 16.3) compared to the control group. There were no differences in the time to/risk of a new episode of LBP in either of the subgroups. Conclusion Data support the use of MC in a stratified care model targeting dysfunctional patients for MC. For a carefully selected group of patients with recurrent and persistent LBP the clinical course becomes more stable and the number of pain-free weeks between episodes increases when receiving MC. Understanding how subgroups of patients are likely to be affected by MC may help align patients’ and clinicians’ expectations based on realistic outcomes. Trial registration Clinical trials.gov; NCT01539863 ; February 22, 2012.